Death and Woman: Comparing the Meaning of the Deaths of the Female Main Characters in the Works of Toni Morrison and Alice Munro - Achmad Munjid (Lexicon, 2019)
This paper seeks to explore the meaning of death in two important works by two female Noble Prize winning authors, Toni Morrison and Alice Munro. Hagin’s (2010) theory of role of death in storyline is used to analyze the works. The three deaths found in the story: initial death, intermediary death and story-terminating death all have significant meaningful relation to the past and the future. They have epistemological value of revealing and/or exposing the truth from the past. Death is used as technical instrument to reveal the truth, to transform ignorance into knowledge, dishonesty into accountability, to purify the past from falsehood and lies. Death also inserts its demand in the story by removing obstacle or giving opportunity for the living to set up new goal. The demand of the dead is possible since the deceased is “remembered” by the “cult” who may follow or manipulate their legacy. The two authors articulate “feminist voice” through the struggle of the main female characters. Toni Morrison articulates the dehumanizing consequence of racism, whereas Alice Munro voices her concern on the contradictory nature of orderly neat appearance of the modern people versus scandalous dark secret beneath the surface.Keywords: dehumanization, feminist voice, initial death, intermediary death, story-terminating death, racism.